Treatment of advanced non-small-cell lung cancer: The 2019 AIOM (Italian Association of Medical Oncology) clinical practice guidelines. (February 2020) - Passiglia, F.; Pilotto, S.; Facchinetti, F.; Bertolaccini, L.; Del Re, M.; Ferrara, R.; Franchina, T.; Malapelle, U.; Menis, J.; Passaro, A.; Ramella, S.; Rossi, G.; et al.
Abstract: The Italian Association of Medical Oncology (AIOM) has developed clinical practice guidelines for the treatment of patients with advanced non-small cell lung cancer (NSCLC). In the current paper a panel of AIOM experts in the field of thoracic malignancies discussed the available scientific evidences, with the final aim of providing a summary of clinical recommendations, which may guide physicians in their current practice.